2021
DOI: 10.15252/embj.2020106412
|View full text |Cite
|
Sign up to set email alerts
|

ArfGAP1 inhibits mTORC1 lysosomal localization and activation

Abstract: The mammalian target of rapamycin complex 1 (mTORC1) integrates nutrients, growth factors, stress, and energy status to regulate cell growth and metabolism. Amino acids promote mTORC1 lysosomal localization and subsequent activation. However, the subcellular location or interacting proteins of mTORC1 under amino acid-deficient conditions is not completely understood.Here, we identify ADP-ribosylation factor GTPase-activating protein 1 (ArfGAP1) as a crucial regulator of mTORC1. ArfGAP1 interacts with mTORC1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 76 publications
(152 reference statements)
0
11
0
Order By: Relevance
“…This process is dependent on ADP‐ribosylation factor GTPase‐activating protein 1 (ARFGAP1). ARFGAP1 binds to mTORC1 to stop lysosomal localisation in the absence of amino acids; overexpression of ARFGAP1 prevents the recruitment of mTORC1 to the lysosomal surface and inhibits downstream signalling, whereas the loss of ARFGAP1 promotes mTORC1 activity, even in the absence of amino acids [ 33 ].…”
Section: The Lysosomal Surface–the Home Of Mtorc1 Activationmentioning
confidence: 99%
“…This process is dependent on ADP‐ribosylation factor GTPase‐activating protein 1 (ARFGAP1). ARFGAP1 binds to mTORC1 to stop lysosomal localisation in the absence of amino acids; overexpression of ARFGAP1 prevents the recruitment of mTORC1 to the lysosomal surface and inhibits downstream signalling, whereas the loss of ARFGAP1 promotes mTORC1 activity, even in the absence of amino acids [ 33 ].…”
Section: The Lysosomal Surface–the Home Of Mtorc1 Activationmentioning
confidence: 99%
“…Two highly connected subgraphs are obtained as shown in Figure 3, which include the following 14 genes: ITG1, HSPA5, ACTB, ATP5F1B, CCT5, GAPDH, ARPC1A, GNA12, ARFGAP1, INS, CDC42, BSG, ARFGAP3, and ARF1. Among these 14 genes, it has recently been reported that ARFGAP1 is a predictive factor for pancreatic cancer [38], and GAPDH has been used as a reference gene in fetal rat pancreas analysis [39]. In Figure S2.4 in Supplementary Additional File 2, only the androgen receptor (AR) transcription factor was reported by Metascape.…”
Section: Resultsmentioning
confidence: 99%
“…4 e). On the other hand, recent reports have revealed a novel role of Arf1 in mTORC1 activation on the amino acid sensing pathway 25 27 . Intriguingly, Arf1 plays an important role in the regulation of mTORC1 by glutamine and asparagine while the well-characterized Rag GTPase pathway mediates mTORC1 activation downstream of leucine, arginine, methionine, and some other amino acids 28 34 .…”
Section: Discussionmentioning
confidence: 99%